The organizing actions of adolescent gonadal steroid hormones on brain and behavioral development. (November 2016) - Schulz, Kalynn M.; Sisk, Cheryl L.
Highlights: Adolescence is a sensitive period for the effects of hormones on brain and behavior. Testicular hormones masculinize and defeminize social and reproductive behaviors. Ovarian hormones have both feminizing and defeminizing effects on female behavior. Gonadal steroid hormones drive many brain structural changes during adolescence. Adolescence may be part of a protracted postnatal steroid-sensitive period. Abstract: Adolescence is a developmental period characterized by dramatic changes in cognition, risk-taking and social behavior. Although gonadal steroid hormones are well-known mediators of these behaviors in adulthood, the role gonadal steroid hormones play in shaping the adolescent brain and behavioral development has only come to light in recent years. Here we discuss the sex-specific impact of gonadal steroid hormones on the developing adolescent brain. Indeed, the effects of gonadal steroid hormones during adolescence on brain structure and behavioral outcomes differs markedly between the sexes. Research findings suggest that adolescence, like the perinatal period, is a sensitive period for the sex-specific effects of gonadal steroid hormones on brain and behavioral development. Furthermore, evidence from studies on male sexual behavior suggests that adolescence is part of a protracted postnatal sensitive period that begins perinatally and ends following adolescence. As such, the perinatal and peripubertal periods of brain and behavioral organization likely do not represent two discrete sensitive periods, but instead are the consequence of normative developmental timing of gonadal hormone secretions in males and females.